The effect of explicit training of metacognitive reading strategies on online reading comprehension - Babashamasi, Parastoo (Arab World English Journal, 2022)
Few studies have investigated the detailed procedure of systematically delivering and teaching metacognitive strategies in higher education. This study investigates whether explicit training in metacognitive strategies could improve undergraduates’ online reading comprehension over the pandemic. The results of this study contribute to teacher education programs to teach and apply regularly metacognitive reading strategies. In a quasi-experimental design, the experimental group and control group underwent 14 sessions of training. Semi-structured interviews and a Metacognitive Reading Awareness Strategy Assessment were conducted among experimental students. The data were collected using the reading test, Metacognitive Reading Awareness Strategy inventory, and semi-structured interviews in Malaysia. The results of Repeated Measure ANOVA showed the mean scores of students in the metacognitive group were significantly higher than the mean score of the students in the conventional reading group (F= 1.3,82.3) = 215.973. p <0.001). The results of the Metacognitive Reading Awareness Strategy Assessment showed that students had more awareness of global reading strategies (M= 3.511), followed by supporting reading strategies (M=3.468) and problem-solving strategies (M= 3.427). The thematic analysis result supported that students were moderate users of planning and monitoring strategies while evaluative ones were less frequent. The results also revealed that students perceived that lack of vocabulary knowledge, heavy dependence on their teachers, and lack of strategy training were the main causes of their reading difficulties. The findings implied that EFL teachers should introduce metacognitive reading strategies through appropriate and systematic instructions to enable the students to implement them in their academic reading.